Efektivitas Penerapan Metode Tanya Jawab dengan Variasi Media Pembelajaran Terhadap Peningkatan Hasil Belajar Siswa dalam Mata Pelajaran PKN Khusus dalam Materi Ideologi Pancasila - Suwela, I Gusti Made (Journal of Education Action Reseach, 2018)
The purpose of this class action research is to determine the effectiveness of the implementation of the Question and Answer Method with a variety of instructional media on improving student learning outcomes in PKN subjects specifically in Pancasila Ideology material in odd grade IV students of SD No. 1 in the 2015/2016 school year. The research subjects in this study were fourth grade students in the odd semester of the 2015/2016 academic year which amounted to 19 students. This research is a classroom action research conducted in three cycles.. Data on student learning outcomes are collected through learning outcomes tests. The collected data was analyzed using descriptive analysis. The results of this study indicate that in the first cycle the number of students was 19 people, who graduated 6 people and those who did not pass 13 people, with an average score of 60.00. The percentage of graduation in the first cycle was 31.58% and the number of graduates was 68.42%, because it did not meet the KKM value standard (65) then the second study was conducted in the second cycle. Data obtained in cycle II with the number of students 19 people, who graduated 16 people and those who did not pass 3 people, with an average value of 66.05 and the percentage of graduation 84.21% and the non-graduation of 15.79%. Because it has not felt complete, the researcher conducted a research again in the third cycle, with the number of students being 19 people, students who passed 19 people with an average value of 68.42% and the percentage of completeness 100%.